The Hegemony of Public Service Practices in the Perspective of Power Dualism of Traditional Villages and Government Villages - I Nengah Merta; Ni Luh Putu Erma Mertaningrum (Universitas Pendidikan Ganesha, 2022)
In Bali, they there know the terms government village and traditional village. In the government village, there are hamlets and neighbourhood heads, the top leader, Perbekel. Traditional villages consist of Banjar, and each has a kelian. The top leader is called the bendesa. Traditional villages have their courts called kerta desa and various regulations, including awig-awig as the basic law, perarem as law, and other regulations. There is a village police called Pecalang to enforce the rules. This dualism often raises the question of how Bali maintains the village's existence in the tendency of increasingly narrow distances, spaces, and boundaries of assimilation between humans, which must be sorted based on the status of traditional krama, krama tamiu, and tamiu. This paper describes the shackles of public services on the dualism axis of power in traditional and government villages. The shackles referred to in this paper illustrate how strong the policy dominance between the traditional and government villages is and the hegemony of public service access policies below the implementation level. The dualism of power, which both have the authority to determine and regulate the society within their sphere of power. The dualism of interests towards the same object in different ways in carrying out service tasks to the community. In the end, it impacts the mechanism of country and community relations between government villages and traditional villages. The public service mechanism with the dualism of power in Bali is unique and attracts readers' attention, especially those outside Bali.